'Nature and I are Two': A Critical Examination of the Biophilia Hypothesis. (1st May 2011) - Joye, Yannick; De Block, Andreas
Abstract : In 1984, Edward O. Wilson proposed the idea that natural selection has resulted in an adaptive love of life-forms and life-like processes ('biophilia') in humans. To date, the idea of biophilia has been viewed as an ultimate explanation of many conservation attitudes in humans. In this paper, we contend that environmental ethics has little to gain from the biophilia hypothesis. First, the notion is open to various and even conflicting interpretations. Second, the empirical findings that do seem to corroborate a more well-defined version of the biophilia hypothesis can often be accounted for by alternative hypotheses. Third, the evolutionary reasoning behind the biophilia hypothesis tends to be unclear, and sometimes even inaccurate.